Computer study of chromatographic separation of mixtures of H-shaped and linear polymers in good and θ-solvents. (8th November 2016) - Wang, Xiu; Limpouchová, Zuzana; Procházka, Karel
Abstract: The general principles of chromatographic separation of mixtures of linear (L) and H-shaped polymers were studied by Monte Carlo simulations. The study focuses on the conditions relevant for experimental chromatography (mild steric confinement, low concentration, etc.). The polymer chains were modeled as self-avoiding walks either in a good or in θ-solvent. The partition coefficient K H is higher than K L in pores with non-attractive walls and the difference ( K H – K L ) in the mixture exceeds that based on values for single-chain systems, but it decreases with increasing | ε w |. For ε w ∗ ca. −0.18, the partition coefficients equal ( K H = K L ) and later their sequence inverts. Evaluation of the concentration profiles and structural characteristics of the chains at different distances from the wall reveals that more deformable linear polymers preferentially accumulate close to the walls and orient parallel with the wall (mainly in the case of attractive walls). Graphical abstract: Highlights: Chromatographic separation of polymer mixtures was simulated by dynamic Monte Carlo. Mixtures of linear and H-shaped polymers in a good and θ-solvent were studied. Study focuses on conditions that are relevant for practical chromatography. Partitioning depends on concentration, solvent quality and interaction with pore wall. Branching compensation adsorption strength doesn't depend on the mixture composition.